Hubungan Konservasi Tanah dan Air Dengan Komoditas yang Diusahakan, Struktur Pendapatan Serta Karakteristik Rumah Tangga (Kasus DAS Cimanuk dan Citanduy) - Agus Pakpahan; Nizwar Syafa'at (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1991)
Sustainable agricultural development cannot be separated from the issue of soil erosion. This research shows that soil erosion is associated with sources of income of the households in the area, commodities being cultivated and demographic characteristics of the household. The higher the proportion of household income from agricultural activities, particularly dryland farming, the higher the erosion in the area. In general, this research suggests that an integrated and comprehensive policy on both commodity and natural resource management and agricultural and non-agricultural, Sectors development is required to solve soil and water conservation problems.